Making sense of the RA security environment within the context of the geopolitical realities of the South Caucasus - Zohrabyan, Eduard; Apinyan, Davit (History and Culture, 2025)
In modern times, in particular, after the 44-day terrorist war unleashed by the Azerbaijani side against the Republic of Artsakh in September 2020, the complex military-political shifts and rearrangements taking place in the South Caucasus, and the Genocide of the Armenians of Artsakh on September 19, 2023, have created serious threats not only to the security and sustainable developments of the Republic of Armenia, but also to the entire region. Scientific research on the fundamental issue goes beyond the scope of purely theoretical interests: it has contemporary practical-political, strategic significance.The article provides an interpretation and critical analysis of the present and the main expectations of the security environment of RA within the context of new geopolitical realignments and dominant interests and activities of geopolitically interested parties.
Keywords: geopolitics; Republic of Armenia; Turkey; Azerbaijan; Georgia; Iran; Russian Federation; South Caucasus; ally; region; relations; contradictions; enemy